IMPLEMENTATION OF WEB-BASED LAUNDRY BARON MANAGEMENT SYSTEM - nurhayani, heni nurhayani; Danov, Kamila; Saputra, Roni; Fitrima Sari, Siska (Ikatan Dosen Menulis, 2024)
The development of information technology has brought significant changes in business management, including in the laundry industry. This research aims to develop and implement a web-based laundry management system that can improve operational efficiency and service quality. This system is designed to overcome various problems in conventional laundry business management, such as manual recording and limitations in report generation. The system was developed using PHP and HTML programming languages and PHP MyAdmin database. The system also allows business owners to monitor business performance in real-time and make more accurate data-based decisions.